Ionization and separation as a strategy for significantly enhancing the thermal stability of an instable system: a case for hydroxylamine-based salts relative to that for pure hydroxylamine. Issue 45 (14th November 2017) - Ma, Yu; He, Xudong; Meng, Liya; Xue, Xianggui; Zhang, Chaoyang
Abstract : Energetic ionic salts (EISs) are attracting extensive attention because of their ready preparation and some excellent properties and performances that are comparable to those of common explosives with neutral molecules. Abstract : Energetic ionic salts (EISs) are attracting extensive attention because of their ready preparation and some excellent properties and performances that are comparable to those of common explosives with neutral molecules. Hydroxylamine (HA) is protonated or ionized as H-HA + and preferred to be introduced into EISs to form HA-based EISs with almost all kinds of anions since these EISs possess higher packing densities and thus more excellent detonation performances than others with the same anions. Moreover, relative to that of pure HA, the thermal stability of HA-based EISs is significantly enhanced. This significantly enhanced thermal stability can extend the application of HA via deprotonation of H-HA + back to HA; however, the mechanism for stabilization of HA by salification remains unclear. Herein, we employed thermodynamic and kinetic calculations and molecular dynamics simulations to reveal the thermal stability mechanisms of many currently synthesized HA-based EISs and some previously reported EISs with inorganic anions as well as those of pure HA and its aqueous solution. As a result, we have found that the enhanced stability of HA-based EISs is mainly due to the ionization and separation of HA molecules themselves. That is, H-HA +, as an ionized product, is more molecularly stable than HA, with significantly strengthened covalent bonds. The separation of H-HA + ions or HA molecules makes decomposition more difficult as decomposition initiation varies from bimolecular to unimolecular reactions of HA, with a significant increase in the energy barrier. We have, therefore, proposed a strategy for the stabilization of unstable systems, such as neutral N-rich energetic compounds, by ionization and separation to strengthen these systems and change the decomposition mechanism by increasing the energy barriers of trigger steps such that these barriers become more difficult to overcome, respectively.